1991
DOI: 10.1111/j.1365-2044.1991.tb11502.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a hygroscopic heat and moisture exchanger for paediatric use

Abstract: SummaryA laboratory study of a widely available heat and moisture exchanger marketed for paediatric use was undertaken. The deadspace, measured by volume displacement, was 12 ml, similar to that of a standard catheter mount for paediatric use. Pressure drop across the device was measured at several different flows in Jive samples of the device in both the dry and wet state.Calculated resistance proved to be markedly lower when compared with that of other anaesthetic equipment such as tracheal tubes, and with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Wilkinson and co-workers investigated the resistance to¯ow for 12 hygroscopic HME in order to determine the possible effects on the work of breathing during steady state anaesthesia. 114 They found the dead space to be equal to standard catheter mounts (12 ml), and they comment that resistance to breathing was`low, compared to other anaesthetic equipment'. The use of some HMEFs in paediatrics has been restricted by the dead space of the devices.…”
Section: Delay or Failure Of Gas Inductionmentioning
confidence: 99%
“…Wilkinson and co-workers investigated the resistance to¯ow for 12 hygroscopic HME in order to determine the possible effects on the work of breathing during steady state anaesthesia. 114 They found the dead space to be equal to standard catheter mounts (12 ml), and they comment that resistance to breathing was`low, compared to other anaesthetic equipment'. The use of some HMEFs in paediatrics has been restricted by the dead space of the devices.…”
Section: Delay or Failure Of Gas Inductionmentioning
confidence: 99%
“…8 11 A modern paediatric HME adds little deadspace or resistance to flow even when fully saturated. 117 Recently, more sophisticated devices have become available that not only have heat and moisture exchanging qualities but that also act as an effective barrier to bacteria and viruses. These heat and moisture exchanging filters (HMEF) use a hydrophobic membrane composed of coated ceramic fibres, which is deeply pleated to maximize surface area and absorption surface.…”
Section: Humidification Of Inspired Gasesmentioning
confidence: 99%
“…It has been demonstrated that the endotracheal tube is the individual component with the highest contribution to airway resistance . Also, breathing circuit filters were shown to contribute—to a lesser extent—to the artificial resistance . However, research on other components of the breathing circuit is lacking or outdated considering the continuously growing product range.…”
Section: Introductionmentioning
confidence: 99%